Effect of plantation management of three exotic species on forest soil recovery in Oxapampa - Peru - Ormachea Ramos, Álvaro M. (2023)
Three small plantations of Eucalyptus grandis (0.9 Ha), Pinus tecunumanii (0.3 Ha) and Cupressus macrocarpa (0.2 Ha) were established on a plot of land that had been used for agricultural purposes until 2004. Fifteen years later, depth of the mulch (Horizon Ao) generated for decomposition of organic matter of litter produced by the forest management practices was measured. In addition, samples were taken from the A1 horizon for analysis of pH, percentage of organic matter, phosphorus and potassium. Mulch deep results suggests low decomposition of vegetal material for Pinus tecunumanii plantations (9.85 cm), middle for Cupressus macrocarpa (6.18 cm) and higher for Eucalyptus grandis (5.91 cm). However, high organic matter values in horizon A1 are recorded in Cupressus macrocarpa (11.72%) and lower but close among them in Pinus tecunumanii (6.62 %) and Eucalyptus grandis (6.55%). A reduction of soil pH from 6.0 to 5.13 is also reported, which has allowed an increment of phosphorus to become disponible. Organic matter decomposition processes are reviewed as a possible explanation for changes on soil acidity in plantations of Pinus and Cupressus, as well as possible relationships with thinning, pruning, and cleaning up of plantations. Conclusion indicates that forest management evaluated on three plantations has reached pH values as well as phosphorus and potassium availability in the generated forest soil, which in accord with references, favor trees cropping.